Air pollution, clean energy and climate change - Cherian, Anilla (Wiley-Blackwell, 2022)
"As a result of the COVID 19 pandemic, irrevocable loss has been experienced in the personal circles that each of us identifies as family/friends and in the intersecting and rippling circles that expand from there. This book has been written in the margins of grief, and in the midst of the real-time widow work of making sure my sons who tragically and brutally lost their beloved father before his time somehow didn't shatter under the weight of sadness. But, writing a foreword for a book that is inextricably interwoven with profound loss also comes with a sense of gratitude for the courage and loyalty of true friends, and for the tireless advocates who have spoken out for climate justice but are now silenced."--